DEVELOPMENT OF MULTIMEDIA LEARNING MEDIA USING CCY (CHANNEL AND YOUTUBE CONTENT) - Ella H Tumaloto; Fikram Adiko (Jambura Journal of Sports Coaching, 2020)
The research objective is to develop multimedia learning media by using the youtube channel on volleyball in SMP Negeri 10 Gorontalo and to determine the feasibility of multimedia learning media by using the youtube channel on volleyball at SMP Negeri 10 Gorontalo. The method used in this study is RD with a procedural development model because this model is descriptive, that is, research that is used to produce certain products, and test the effectiveness of these products. The number of research subjects was 223 students with a sample of 143 students consisting of 74 male and 69 female. Expert validation was carried out by 2 experts and one physical teacher. Based on the hypothesis test, a t-count of 16.75 is obtained so that it can be stated that the use of learning media CCY (Channel and Content Youtube) on the basic passing techniques in volleyball games in SMP Negeri 10 Gorontalo can be accepted and used in the learning process of Physical Education especially in basic technical material. passing in a volleyball game.